2016
DOI: 10.1111/idh.12221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of parental awareness regarding their child's oral hygiene

Abstract: Many parents were not aware of their child's oral hygiene. Educational interventions should be provided to young families to increase parental knowledge and skills that help them recognize their child's dental needs. The interventions are more necessary for low socioeconomic parents and for the parents of children with poor oral hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
3
20
0
1
Order By: Relevance
“…Concerning degree of cooperation and parents’ educational attainment, our results showed high correlation between educational level of parents and cooperation of children both in t0 and in t4, demonstrating that cooperation might be particularly influenced by this feature. These findings are in accordance with those in literature (47), even if we investigated merely educational level, whereas cited works deeply analysed more aspects of socio-economic status of parents related to oral hygiene maintenance of children. However, educational attainment of parents was found to not affect substantially the cooperation level of children in t4, in fact it evenly increased in SG in all patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Concerning degree of cooperation and parents’ educational attainment, our results showed high correlation between educational level of parents and cooperation of children both in t0 and in t4, demonstrating that cooperation might be particularly influenced by this feature. These findings are in accordance with those in literature (47), even if we investigated merely educational level, whereas cited works deeply analysed more aspects of socio-economic status of parents related to oral hygiene maintenance of children. However, educational attainment of parents was found to not affect substantially the cooperation level of children in t4, in fact it evenly increased in SG in all patients.…”
Section: Discussionsupporting
confidence: 92%
“…Children are more at risk of dental decay onset because of lack of cooperation and difficulty in daily oral hygiene performing (14). Furthermore, evidences show that, even today, many children do not visit a dentist before of development of permanent teeth14 and it seems to be especially related to socio-economic level of families and to knowledge about the dental care needing in childhood (47,15). In order to better investigate these issues, literature suggests to administer questionnaires to parents and several studies have assessed caries risk by using surveys about oral hygiene habits and attendance at dental visits, as well as about parents carefulness in early detecting teeth diseases (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in the present study confirmed that educated parents with better financial status follow better parental practices as in other studies. [15283334353637] It was also found that many studies conducted in various countries have concluded that parents with low educational status with lower income levels were important indicators for the parental practices (dietary and hygiene) among their children. [338] In conclusion, the postulated theory for this could be that reduced education status reduces the financial status which resulted in limited access to the dentists on a regular basis.…”
Section: Discussionmentioning
confidence: 99%
“…They should be educated to realize their children's dental needs, especially for those low-socio-economy parents and whose children with poor oral hygiene. 37 It was reported that teenagers whose parents had high educational achievement used flossing regularly. 38 Previous studies have revealed that educational pattern videos, lectures and pamphlets for the parents and children exerted similar effect on reducing the plaque index.…”
mentioning
confidence: 99%